Graphene and graphene/carbon black composite-based counter electrodes for platinum-free dye-sensitized solar cell - Abdgalil, Ali Khalifa (2021)
The role of the counter electrode in the dye-sensitized solar cell (DSSC) mechanism is to collect the electrons received from the external circuit, and mainly to catalyse the reduction of tri-iodide ions in the electrolyte system. The faster tri-iodide reduction, the faster oxidized dye molecules are regenerated, and thus better DSSC performance. Typically, a platinum catalyst layer is used as a counter electrode in DSSC due to its high conductivity, stability and electrocatalytic activity. However, platinum is a rare and expensive material which prohibit its application for mass production of DSSC. It also corrodes when exposed to the iodine-based electrolyte, which therefore affect the longterm stability of the cell. For the aim of DSSC commercialization, extensive researches have been conducted to reduce the cost of DSSC by introducing effective and low-cost alternative materials. Carbon-based materials DSSC counter electrodes have attracted great interest as alternatives for Pt due to their low-cost, conductivity, catalytic activity, and chemical stability. Recently, owing to its superior electrical conductivity and high crystallinity, graphene was studied as DSSC counter electrode. Though, its catalytic activity for tri-iodide reduction is still considered low. The carbon black also exhibits high electrical conductivity, but with high electrocatalytic activity for tri-iodide reduction due to its higher surface area. Thus, it is expected that Graphene/ Carbon black composites would show higher catalytic activity and better performance as DSSC counter electrode and being promising alternative to replace the expensive platinum in DSSCs. This research started with optimization of the single-layer screen-printed TiO2 photoanode, and then is intended to investigate the application of low-cost and effective Graphene and Graphene/Carbon black (G/Cb) composites counter electrodes for DSSC. Graphene counter electrodes were prepared by drop-casting the diluted graphene dispersion on FTO-coated glass substrates. The study focused on the effect of heat treatment of the graphene-based counter electrode on the DSSC performance. Moreover, to enhance the electrocatalytic activity of the graphene electrodes, six different G/Cb composites-based counter electrodes were screen-printed on FTO-coated glass using six different pastes composing of varied graphene to carbon black powders ratios. For comparison, screen-printed Solaronix carbon paste and platinized-FTO were used as reference counter electrodes. Different characterizations and measurements were undertaken to investigate the applicability of the proposed graphene and G/Cb electrodes to serve as counter electrodes in DSSCs. The graphene film with a thickness of ca. 25 μm and heated at 300⁰ C possesses good adhesion and low sheet resistance 18.3 Ω/□ which was a promising value compared to other electrodes (as-deposited, 100⁰ C, and 200⁰ C). Hence, the DSSC used graphene electrode heated at 300⁰ C shows power conversion efficiency of 3.32%, comparable to 4.48% obtained from Pt-based DSSC. The obtained power conversion efficiency was attributed to the high electrical conductivity of the graphene electrodes although they possess low electrocatalytic activity for tri-iodide reduction. Further, the results showed that the DSSC based on CB40 composite exhibited maximum power conversion efficiency of 4.58% and fill factor of 0.56 with higher electrocatalytic activity than the graphene electrode. The achieved result is comparable to those shown by DSSCs using Pt and Solaronix carbon paste of 5.19 and 3.67 with fill factors 0.66 and 0.61, respectively. The low-cost, high conductivity and the porous structures of the introduced graphene and graphene/Carbon black counter electrodes make them potential candidates to replace the expensive platinum counter electrode.